Students’ Learning Difficulties: a Correlational Study on the Influence of Teachers’ Social Competence - Sari, Melinda Novita; Khasanah, Uswatun; Romlah, Listiyani Siti (Journal of Innovation and Research in Primary Education, 2025)
This study explores the influence of teachers' social competence on students' learning difficulties in Madrasah Tsanawiyah (MTs) Al Hidayah, Tunggul Pawenang, Pringsewu. The research utilizes a quantitative correlational approach, focusing on the relationship between teachers' social competence and the learning challenges faced by students. A survey was conducted with 70 students from class VIII using validated and reliable questionnaires. The results indicate a significant correlation between teachers' ability to communicate effectively, show empathy, and create a supportive learning environment, and the reduction of students' learning difficulties. Specifically, teachers who establish positive relationships and facilitate open communication create a more conducive learning atmosphere, enhancing students' confidence and participation. Conversely, teachers with lower social competence tend to experience more significant barriers in addressing students' academic challenges. The findings suggest that improving teachers' social competence can be an effective strategy to mitigate learning difficulties, especially in environments with diverse cultural and social backgrounds. This research contributes to the literature on teacher-student interaction, emphasizing the importance of teachers' emotional and social skills in fostering inclusive and effective learning environments. Furthermore, the study calls for teacher training programs that enhance both pedagogical and social competencies to optimize student learning outcomes in Islamic educational settings.